Spiritualitas Makan Bersama: Interkoneksi Sesama Ciptaan dalam Praktik Pemeliharaan Alam - Christina Dameria; Dewi Sintha Bratanata (IAKN Ambon, 2021)
Eating together is a culture that was born along with human civilization. Eating together becomes a symbol in both religious and cultural rituals. Christianity notes that eating together becomes a medium in spreading the gospel that Jesus and His disciples did. The symbolic meaning presented in the practice or culture of eating together is acceptance and fellowship. Acceptance is defined as a space to acknowledge the equality of fellow human beings, which creates a sense of solidarity. At the same time, the fellowship provides space to connect. In addition, eating together fulfills the body's physical needs for hunger and restores the freshness of the soul from fatigue. This article tries to connect symbols in eating together to present spirituality in viewing other creations, namely nature that has been damaged. Natural damage needs to be seen as a reality that must be faced and resolved t in the spirituality of eating together.Â Another creation is nature being the poor, oppressed, marginalized and sick. The solidarity presented in the moment of eating together becomes a new perspective in seeing the context of the destruction of nature and the awareness to build the disconnected interconnection of fellow creations.AbstrakMakan bersama merupakan budaya yang lahir seiring dengan peradaban manusia. Makan bersama menjadi simbol baik dalam ritual keagamaan maupun budaya. Kekristenan mencatat bahwa makan bersama menjadi sebuah media dalam mengabarkan Injil yang dilakukan Yesus dan para murid-Nya. Makna simbolik yang dihadirkan dalam ritual atau budaya makan bersama adalah penerimaan dan persekutuan. Penerimaan diartikan sebagai sebuah ruang untuk mengakui adanya persamaan terhadap sesama manusia yang menimbulkan rasa solidaritas. Sedangkan persekutuan memberikan ruang untuk saling terhubung satu dengan yang lain. Selain itu makan bersama tidak sekadar memenuhi kebutuhan fisik tubuh akan rasa lapar tetapi juga mengembalikan kesegaran jiwa akan rasa lelah. Artikel ini mencoba menghubungkan simbol-simbol dalam makan bersama untuk menghadirkan spiritualitas dalam memandang ciptaan lain yaitu alam yang telah rusak. Kerusakan alam perlu dipandang sebagai sebuah kenyataan yang harus dihadapi dan diselesaikan bersama dalam spiritualitas makan bersama. Ciptaan lain yaitu alam menjadi yang miskin, tertindas, tersingkir dan sakit. Solidaritas yang dihadirkan dalam momen makan bersama menjadi sebuah perspektif baru dalam melihat konteks kerusakan alam dan kesadaran untuk membangun interkoneksi sesama ciptaan yang terputus.